Nanomaterials-Based Optical Techniques for the Detection of Acetylcholinesterase and Pesticides - Ning Xia; Qinglong Wang; Lin Liu (Sensors, 2014)
The large amount of pesticide residues in the environment is a threat to global health by inhibition of acetylcholinesterase (AChE). Biosensors for inhibition of AChE have been thus developed for the detection of pesticides. In line with the rapid development of nanotechnology, nanomaterials have attracted great attention and have been intensively studied in biological analysis due to their unique chemical, physical and size properties. The aim of this review is to provide insight into nanomaterial-based optical techniques for the determination of AChE and pesticides, including colorimetric and fluorescent assays and surface plasmon resonance.